Peningkatan Hasil Belajar Matematika Peserta Didik Pada Model Problem Based Learning (PBL) Kelas IX SMP Negeri 13 Mataram Semester Ganjil Tahun Ajaran 2024/2025 - Juliyanti; Kertiyani, Ni. Made Intan; Nugroho, Slamet (Mataram University, 2025)
This classroom action research (CAR) aims to examine the improvement of students’ mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model on the topic of exponents. The study was conducted in class IX-G of SMP Negeri 13 Mataram during the first semester of the 2024/2025 academic year, involving 32 students as research subjects. The research was carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected through direct observation by the observer during the learning process and through students’ cognitive achievement tests administered at the end of each cycle. The data were analyzed using descriptive statistical techniques, with the indicator of success being an increase in the average mathematics learning outcomes in each cycle. The results showed a significant improvement in students’ mathematics performance after implementing the PBL model. In the first cycle, the average percentage score of students’ learning outcomes was 56%, which increased to 78% in the second cycle. Therefore, it can be concluded that the Problem Based Learning (PBL) model has a positive and effective impact on improving students’ mathematics learning outcomes in class IX of SMP Negeri 13 Mataram.